Analysis of the Carrying Capacity of the Pile Foundation Compared to Jacking System and Pile Driving Analyzer (PDA) Test - Choirus Soleh Rozeli (NAROTAMA UNIVERSITY, Indonesia)
The foundation is a structure under the building that serves as a distributor of the load on it to the supporting ground layer. The pile capacity is obtained from the soil investigation results which is a sondir test. Sondir test is a technique of soil layer estimator to determine the type of foundation that will be used such as pile foundation. Hydraulic Jacking System is a equipment to pressure the pile. Pile Driving Analyzer Test is a system used for test the pile dynamically after erection. The purpose of this research is to know the method of bearing capacity of pile foundation calculation based on sondir data which approach Hydraulic Jacking System capacity and Pile Driving Analyzer Test capacity. This research method is quantitative. Data were collected using survey techniques. The survey technique is used to obtain generat data from the field. The data is processed using Schmertmann’s method, Philipponant’s method, and Andina’s method, and the results is compared with the Hydraulic Jacking System capacity and Pile Driving Analyzer Test capacity.